1970
DOI: 10.1677/joe.0.0460093
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Protein-Depleted Rats

Abstract: Renal iodide clearance in rats was reduced rapidly when the animals were fed a protein-depletion diet. If the iodine content of the protein-depletion diet is high, this results in an increase in the serum iodide levels to concentrations in excess of 150 \g=m\g./100 ml. Protein-bound iodine was elevated due to the accumulation of iodinated serum albumin. Thyroid hormonal iodoamino acid content was transiently depressed, presumably by the mechanism described by Wolff & Chaikoff (1948). Thyroxine metabolism was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Recent measurements of plasma free T4 showed normal or elevated results in kwashiorkor, and normal or low levels in marasmus (Graham et af., 1973). Thyroid 13'1 uptake is reported as reduced or normal in marasmus (Beas et af., 1966), and normal in kwashiorkor (Gopalan, 1969), but interpretation may be complicated by impairment of iodide clearance as shown in experimental models (Florsheim et al, 1970). There have, however, been reports of deficient organification of iodide with abnormal perchlorate discharge (Gopalan, 1969) and an abnormally high MIT, DIT: T3, T4 ratio in human plasma (Godard & Lemarchand-Beraud, 1973) and rat thyroid (Florsheim et al, 1970) as well as a low thyroid to serum radioiodide concentration ratio in animals (Srebnik et al, 1963;Cowan & Margossian, 1966).…”
Section: P I T U I T a R Y -T H Y R O I D F U N C T I O Nmentioning
confidence: 99%
“…Recent measurements of plasma free T4 showed normal or elevated results in kwashiorkor, and normal or low levels in marasmus (Graham et af., 1973). Thyroid 13'1 uptake is reported as reduced or normal in marasmus (Beas et af., 1966), and normal in kwashiorkor (Gopalan, 1969), but interpretation may be complicated by impairment of iodide clearance as shown in experimental models (Florsheim et al, 1970). There have, however, been reports of deficient organification of iodide with abnormal perchlorate discharge (Gopalan, 1969) and an abnormally high MIT, DIT: T3, T4 ratio in human plasma (Godard & Lemarchand-Beraud, 1973) and rat thyroid (Florsheim et al, 1970) as well as a low thyroid to serum radioiodide concentration ratio in animals (Srebnik et al, 1963;Cowan & Margossian, 1966).…”
Section: P I T U I T a R Y -T H Y R O I D F U N C T I O Nmentioning
confidence: 99%
“…Whether the decreased rate of secretion from the thyroid observed during feed restriction can be considered due to a decrease in TSH secretion, or a lack of response of the thyroid to circulating TSH, or both, is unclear. In man SUbjected to protein-caloric malnutrition, and in protein-depleted rats, no changes in circulating TSH were observed (Florsheim et al 1970;Chopra and Smith 1975). However, normal.…”
Section: Discussionmentioning
confidence: 92%
“…The cause of this decrease is not clearly established, since measurements of circulating TSH in rats and humans on inadequate diets which depress thyroid secretion do not necessarily show reduced TSH concentrations (Srebnik et al 1963;Florsheim et al 1970;Chopra and Smith 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Several workers have observed the involution of the thyroid gland in mal-nourised rats [12][13][14][15]. It was also reported that the pituitary TSH content was reduced by protein deprivation in rats 16.17).…”
Section: Resultsmentioning
confidence: 99%